Evaluation of Seed Quality of Chickpea (Cicer arietinum L.) Collected from Different Branches - Khatun, A; Bhuiyan, MAH (Bangladesh Journal of Scientific and Industrial Research, 2012)
Mature seeds of three chickpea varieties like BARI Chhola-5, 6 and 8 were collected from three different branches like primary, secondary and tertiary, and were evaluated for quality in the Seed Technology Laboratory, Bangladesh Agricultural Research Institute, Gazipur, Bangladesh during August to September of 2004 and 2005. All the seeds were stored in earthen pot for five months before conducting the laboratory study. Significant variation was observed in all three varieties of chickpea for all the parameters studied except seed vigour. The highest moisture percentage (10.17 in 2004 and 10.18 in 2005), dry weight (0.50 g in 2004 and 0.51 g in 2005) and seed vigour (39.7 in 2004 and 41.6 in 2005) was observed in BARI Chhola-8 and the lowest in BARI Chhola-5. Germination percentage was significantly higher in BARI Chhola-5 (87.6 in 2004 and 88.9 in 2005). Seeds of different branches did not vary significantly for most of the parameters. However, seeds of primary or secondary branches had higher moisture and germination percentage, dry weight of seedling and seed vigour. Interaction effects of varieties and seeds of different branch had no definite trend though non-significant effect was observed in most of the parameters. Keywords: Chickpea; Seed of different branches; Vigour; Moisture; Germination DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9599 BJSIR 2011; 46(4): 507-512